Fengshi Gutong Capsule Attenuates Osteoarthritis by Inhibiting MAPK, NF-κB, AP-1, and Akt Pathways - Gao, Yao-Xin; Yu, Hao-Heng; He, Chuan; Li, Ming; Guo, Dan-Dan; Lian, Jun-Jiang; Yang, Hai-Jie; Wang, Mian; Wang, Lei; Feng, Zhi-Wei; Cheng, Bin-Feng (Frontiers in Pharmacology, 2018)
Background and purpose: Fengshi Gutong capsule (FSGT), a traditional herbal formula, has been used clinically in China for the treatment of arthritis. However, the mechanism underlying the therapeutic effects of FSGT on osteoarthritis (OA) has not been elucidated. The present study investigated the function and mechanisms of FSGT in rat OA model, and interleukin (IL)-1β-stimulated synovial cells. Materials and methods: Rat OA model was established by intra-articular injection with 4% papain. IL-1β-induced SW982 cells were used as a cell OA model. Safranin-O-Fast green (S-O) and hematoxylin-eosin (HE) stainings were used to observe the changes in cartilage morphology. Enzyme-linked immunosorbent assay (ELISA) and real-time quantitative PCR (qPCR) were used to detect the expression of inflammatory cytokines. In addition, molecular mechanisms were analyzed by Western blot in the OA cell model. Results: FSGT (200 and 400 mg/kg) treatment significantly relieved the reduction of cartilage matrix and reduced tumour necrosis factor (TNF)-α and IL-6 levels in the serum in papain-induced OA rats. FSGT (200 and 400 mg/mL) also significantly inhibited the protein and mRNA levels of IL-6 and IL-8 in IL-1β-induced SW982 cells. Moreover, FSGT inhibited phosphorylation levels of ERK (extracellular signal-related kinase), JNK (c-Jun N-terminal kinase), p38, Akt (protein kinase B), and c-Jun. It also decreased IκB-α degradation and p65 protein translocation into the nucleus. Conclusion: The current data confirmed the protective effects of FSGT in the rat and cell OA models. The results suggested that FSGT reduced the production of inflammatory mediators via inhibiting the activation of mitogen-activated protein kinases (MAPK), nuclear factor (NF)-κB, activator protein (AP)-1, and Akt.